Acute onset of blisters in an infant with acrodermatitis enteropathica: A case report. (April 2021) - Cleminson, Kristyna; Hull, Peter R; Price, Emma; Green, Peter J
We represent a pediatric case of the congenital disorder caused by zinc malabsorption, acrodermatitis enteropathica, presenting with acute onsetof blisters. Although blisters can be seen in this condition, it is not always a key feature and can therefore be overlooked when considering a differential diagnosis of acute blistering in infancy. We therefore review the common and less common features of this cutaneous eruption as well as provide an extensive differential diagnosis for acute blistering in infancy. We also emphasize the importance of lifelong treatment with zinc supplementation in these children.